The Perfection of Horse-Manship: Review of Monica Mattfeld, Becoming Centaur:Eighteenth-Century Masculinity and English Horsemanship - Nash, Richard (Humanimalia, 2017)
Monica Mattfeld. Becoming Centaur: Eighteenth-Century Masculinity and English Horsemanship. University Park, PA: Penn State University Press, 2016. 288 pp. 99.95 (hc).